Real-Time Ultrasound Image Fusion with FDG-PET/CT to Perform Fused Image-Guided Fine-Needle Aspiration in Neck Nodes: Feasibility and Diagnostic Value - de Koekkoek-Doll, P.K.; Maas, M.; Vogel, W.; Castelijns, J.; Smit, L.; Zavrakidis, I.; Beets-Tan, R.; van den Brekel, M. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: New imaging techniques such as hybrid imaging of ultrasound and FDG-PET/CT are available but not yet investigated for node staging. The aim of the study was to evaluate the feasibility and added diagnostic value of real-time image-fused ultrasound-guided fine-needle aspiration with FDG-PET/CT data for node staging.MATERIALS AND METHODS: Ninety-six patients who were referred for cervical lymph node staging with FDG-PET/CT before ultrasound were prospectively included. After routine ultrasound-guided fine-needle aspiration, all FDG-PET-positive nodes were marked on FDG-PET/CT, and real-time image fusing of ultrasound and FDG-PET/CT was performed using the electromagnetic navigation system PercuNav. Already-punctured nodes were confirmed to be PET-positive, and additional fused-ultrasound-guided fine-needle aspiration was performed in previously missed PET-positive nodes.RESULTS: Of 96 patients, 87 (91%) patients had suspicious nodes requiring fine-needle aspiration cytology. Ultrasound-guided fine-needle aspiration was performed in 175 nodes. Cytology was inconclusive in 9/175 (5%) nodes, and 85/166 (51%) nodes were malignant. Target planning was performed in 201 PET-positive nodes; 195/201 (97%) of those nodes were fused successfully. Twenty of 175 ultrasound-guided fine-needle aspiration nodes turned out to be FDG-PET-negative, and 149/175 (85%) of the fused ultrasound-guided fine-needle aspiration nodes were confirmed to be FDG-PET-positive. Of 201 PET-positive nodes, 46 (23%) were additionally identified, and fused ultrasound-guided fine-needle aspiration was performed. Cytology was inconclusive in 4/46 nodes (9%), and 13/42 (31%) nodes were malignant.CONCLUSIONS: Real-time ultrasound image fusion with FDG-PET-positive nodes is feasible in cervical lymph nodes, and fused ultrasound-guided fine-needle aspiration increases the number of malignant nodes detected.cN0clinically node-negative neckFNACfine-needle aspiration cytologyHNChead and neck cancerNDneck dissectionTNMTumor, Node, MetastasisUSultrasoundUSgFNACultrasound-guided fine-needle aspiration cytology